THE UNIVERSAL DECLARATION OF INFORMATION RIGHTS OF SOCIETY AS A BASIS OPPOSITION TO THE FORMATION OF TOTALITARIAN REGIMES - Matviichuk, Andrii; Mykulets, Vitalii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Aim: conceptualization of the idea of the Universal Declaration of Information Rights of Society. In this regard, the following tasks are implemented in the presented material: 1) to outline the factual and legal prerequisites for emergence of the Universal Declaration of Information Rights of Society; 2) to provide a description of the functional load of the proposed Declaration as an international document; 3) to show a possible mechanism for the practical implementation of the idea of the Universal Declaration of Information Rights of Society. Research methods are the following: general theoretical and analytical methods combined with systemic and complex approaches. Results: it was established at the theoretical level of the study, that historical practice proves the danger of the formation of totalitarian regimes in connection with the violation of personal and public informational rights. The Universal Declaration of Information Rights of Society has been identified as a promising means of countering the formation of totalitarian regimes, which will contain the establishment of relevant rights, as well as the procedures for bringing a certain state to political, economic, international and legal responsibility (by imposing systemic sanctions) in case of violation of the specified rights and freedoms. Discussion: the idea of the Universal Declaration of Information Rights of Society is based on two principled positions. Firstly, it is a practically proven absence of effective legal mechanisms of political, economic and international legal responsibility in connection with the violation of human rights and freedoms (in particular, informational ones). Secondly, we need the conviction, because today it is necessary to take a meaningful approach to the development of the post-war world, in particular, in terms of developing safeguards against the emergence of new fascist social formations and threats arising from them.